RANCANG BANGUN SISTEM INFORMASI PEMETAAN BUKU PERPUSTAKAAN SMA NEGERI 6 BEKASI BERBASIS WEB DENGAN METODE WATERFALL - Muhammad Fiqri Alfayed (2021)
SMA Negeri 6 Bekasi has an extensive library and accommodates complete and varied library materials. The large number of library materials that are accommodated causes students to have difficulty finding the library materials needed in the library. This research was conducted to provide a solution, namely the construction of a web-based book mapping information system in the library of SMA Negeri 6 Bekasi using the waterfall method. The expected results from the implementation of the book mapping information system are to make it easier for students to find the library materials needed and available in the library.